Increased Serum S100B Levels in Patients With Epilepsy: A Systematic Review and Meta-Analysis Study - Liang, Kai-Ge; Mu, Rong-Zheng; Liu, Yu; Jiang, Dan; Jia, Tian-Tian; Huang, Yao-Jiang (Frontiers in Neuroscience, 2019)
IMPORTANCE Accumulating evidence suggests that serum levels of S100B may play a role in epilepsy. OBJECTIVE We performed a meta-analysis to quantitatively summarize the serum S100B data available for patients with epilepsy. DATA SOURCE Two independent researchers conducted a systematic s investigation of Harvard Hollis+, Open Grey, Clinicaltrials, Wanfangdata and CNKI databases through February 8, 2018, for all studies published in English and Chinese. The search terms included S100B, Calcium-binding protein B in combination with Epilepsy. STUDY SELECTION Original studies and reported data from these search terms are included. Studies that data were overlapped with other studies were excluded. DATA EXTRACTION AND SYNTHESIS Investigators extracted, pooled and analysed data from the included studies using a Fixed-effects model in the Comprehensive Meta-Analysis3.3 and R software. MAIN OUTCOMES AND MEASURES Peripheral blood levels of S100B in patients with epilepsy compared with controls. Aberrations in Peripheral blood levels of S100B were hypothesized to be related to epilepsy. RESULTS A fixed -effects meta-analysis of all 18 studies, including 1057 unique participants, indicated that patients with Epilepsy had significantly increased peripheral blood levels of S100B compared to controls (Hedges g = 1.568, 95% CI =1.431-1.706, P 0.001). Sensitivity analysis showed that no single study significantly influenced the overall association of peripheral blood levels of S100B and the Epilepsy. Most of the subgroup analyses, including those of Country, assay type and publication language, demonstrated a statistically significant association between peripheral blood levels of S100B and the Epilepsy. Meta-regression analyses indicated that suggesting that more Gender and Mean age might present serum S100B reductions, but samples size, years, assay type, publication language and country did not show moderating effects on the effect sizes. Furthermore, the trim-and-fill method used to adjust for funnel plot asymmetry in our meta-analysis confirmed that a positive outcome is unlikely to be due to publication bias. CONCLUSION AND RELEVANCE The results of this meta-analysis provide evidence for a significant increase in serum S100B levels in patients with Epilepsy. Serum S100B is the most worthwhile biomarker of Epilepsy, which is helpful for the clinical diagnosis and prognosis of epilepsy.